Synthesis and Antimicrobial Activity of 7-Amino cephalosporanic Acid Derivatives of Amino Acids and Peptides - Himaja, M.; Desai, Siddharth; Thirugnana Sambanthan, A.; Ranjitha, J. (Asian Journal of Chemistry, 2010)
A novel series of 7-amino cephalosporanic acid derivatives of amino acid and peptides were synthesized by solution phase technique. The synthesized compounds were tested for their biological activities against bacterial and fungal organisms. All the compounds showed potent antifungal activity and most of the compounds have shown moderate antibacterial activities. The structures of the newly synthesized compounds were confirmed by IR, 1H NMR and mass spectral analysis.